PENGUKURAN LAJU PAPARAN RADIASI PADA RUANG CT-SCAN - Devi Febriana Putri; Sudiyono (Perhimpunan Radiografer Indonesia (PARI), 2018)
Background : CT-Scan is an imaging modality in the field of diagnostics, especially radiology that produces large radiation, so should pay attention to aspects of protection and radiation safety for radiographers and public. At the CT-Scan examination room at Radiology Installation of RSUD Ir. Soekarno has made door replacement and addition of 2 mm Pb on the window and has not done measurement of exposure rate of re-radiation.This study aims to determine the value of the radiation exposure rate and the safety of the examination room on radiation exposure for radiographers and public reffering to the publication of NCRP no. 147 on the design of protective structures for health facilities Methods: This type of research is quantitative with survey approach. This research was conducted in May 2018. Data collection was done by observation, documentation, measurement of exposure rate at a number of points. Data analysis was done descriptively by comparing data with NCRP report no 147. Result: The radiation exposure measurements resulted in excessive radiation exposure in the controlled area at point A (the Pb glass in the operator’s room) of 29,5 µSv/h the uncontrolled area at point 1 (patien’s entrance) of 1,75 µSv/h. This value exceeds the recommendation value of NCRP no. 147 at controlled area of 2,5 µSv/h and uncontrolled area of 0,5 µSv/h. Radiology Installation Ir. Soekarno Sukoharjo Hospital regency is located at an altitude of 103 mdpl the background radiation exposure value of 1,225 µSv/h, it exceeds the requirements of the background exposure rate value according to UNSCEAR for a height of 0 meters from sea level is 0.03 μGy/h. Leakage of radiation exposure occurring at point Conclution: point A isa Pb glass in the operator’s room and at point 1 is patien’s entrance is not safe for radiographers and public because it exceeds the limit of radiation exposure rate value which is allowed